2019
DOI: 10.1038/s41467-019-10631-0
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer self-assembly of pillared two-dimensional multilayers

Abstract: We report Layer-by-Layer (LbL) self-assembly of pillared two-dimensional (2D) multilayers, from water, onto a wide range of substrates. This LbL method uses a small molecule, tris(2-aminoethyl) amine (TAEA), and a colloidal dispersion of Ti 3 C 2 T x MXene to LbL self-assemble (MXene/TAEA) n multilayers, where n denotes the number of bilayers. Assembly with TAEA results in highly ordered (MXene/TAEA) n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(167 citation statements)
references
References 49 publications
5
152
0
Order By: Relevance
“…As shown from the Ragone plot in Figure d, impressively, the MCFs nanomaterials‐based SC displays the maximum energy density of 147.5 mWh cm −3 at a power density of 0.15 W cm −3 , and energy density can be still maintained 94.1 mWh cm −3 at a higher power density of 15 W cm −3 . To the best of our knowledge, the energy density value is evidently one of the best levels among flexible SCs, including commercial Li thin‐film battery, graphene of 2.5 mWh cm −3 , Mxene of 5.1 mWh cm −3 , CNT/graphene of 6.3 mWh cm −3 , porous carbon of 8.4 mWh cm −3 , MnO 2 /carbon cloth of 8.25 mWh cm −3 , polyaniline/graphene of 8.8 mWh cm −3 and MnOx/TiN nanowires/carbon nanotube of 61.2 mWh cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown from the Ragone plot in Figure d, impressively, the MCFs nanomaterials‐based SC displays the maximum energy density of 147.5 mWh cm −3 at a power density of 0.15 W cm −3 , and energy density can be still maintained 94.1 mWh cm −3 at a higher power density of 15 W cm −3 . To the best of our knowledge, the energy density value is evidently one of the best levels among flexible SCs, including commercial Li thin‐film battery, graphene of 2.5 mWh cm −3 , Mxene of 5.1 mWh cm −3 , CNT/graphene of 6.3 mWh cm −3 , porous carbon of 8.4 mWh cm −3 , MnO 2 /carbon cloth of 8.25 mWh cm −3 , polyaniline/graphene of 8.8 mWh cm −3 and MnOx/TiN nanowires/carbon nanotube of 61.2 mWh cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al have reported the preintercalation of CTAB into Ti 3 C 2 T x to realize the reversible insertion of Mg 2+ , thus achieving excellent volumetric performance and rate capability for magnesium ion batteries, and this indicates the possible wide use of surfactant preintercalation in the field of energy conversion and storage 72. In addition to the surfactants, small molecules like tris(2‐aminoethyl) amine (TAEA) was also reported as the interlayer pillaring component for the layer‐by‐layer self‐assembly of Ti 3 C 2 T x MXene 73…”
Section: The Mxene Assembliesmentioning
confidence: 99%
“…This system achieved a specific capacitance of 370 F g À1 at 2 mV s À1 and retained more than 86% over 10,000 cycles (at a specific current of 3 A g À1 ), a great improvement compared with the non-LbL control systems (Table 1). 71 It was later demonstrated that a multilayered system of MXene and multiwall carbon nanotubes (MWCNT) could be prepared by spray-LbL assembly on polycaprolactone (PCL) substrates. 30 PEI was grafted onto the MWCNT to impart a positive charge to oppose the negative Ti 3 C 2 T x , enabling LbL assembly.…”
Section: Reviewmentioning
confidence: 99%
“…30 LbL-assembled Ti 3 C 2 T x MXene composite films exhibit lower conductivities than pure Ti 3 C 2 T x MXene films due to the presence of relatively thick layers of insulating polymers between the MXene flakes introduced during the LbL process. To improve the conductivity of LbL Ti 3 C 2 T x MXene composite films, Tian et al used positively charged tris(2-aminoethyl)amine small molecules rather than polymers to reduce the interlayer spacing of the MXene flakes and achieved a high conductivity (7.3 3 10 4 S m À1 ) for this LbL composite film, 71 although still below the reported value for pristine Ti 3 C 2 T x MXene films (8 3 10 5 S m À1 ). 7 Nevertheless, the relatively high conductivity of the film resulted in superior volumetric capacitance and capacitive rate capability as compared with PEI/MXene LbL films (Table 1).…”
Section: Reviewmentioning
confidence: 99%